The Effect of Medical Tourism Motivation and Psychological Distance on Perceived Risk and Revisit Intention - Focusing on Chinese Medical Tourists - Ko, Seon-Hee (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: This research tries to examine the effect of medical tourism motivation and psychological distance on perceived risk and revisit intention using Chinese medical tourists.